Aggregate versus industry-specific sources of economic growth and business cycle fluctuations - Paavo Peisa (Bank of Finland, 1989)
This paper evaluates the power of aggregate and sector-specific disturbances ta output growth in the Finnish econc:Jrqy using armual data on the growth of value added in 31 industries over the period 1961-87. The unifonn power distribution assumptions implicit in the standa.J:d randam and fixed effects m:rlels are considered and tested by analyzing the power of disturbances by frequency band.
URN:NBN:fi:bof-201807301766
Keywords: 330